Assessment centers in human resource management strategies for prediction, diagnosis, and development - Thornton, George C. (Mahwah, NJ. Lawrence Erlbaum Associates, 2006)
The theme permeating this book on assessment centers is "continuity and change", describing what has remained the same and what has changed in the 50-year history of the assessment center method. One of the important changes explored is the evolution of the goals of assessment center programs and the ways in which assessment centers and their component parts have been used. Assessment Centers in Human Resource Management clearly differentiates between assessment centers used for prediction, diagnoses, and development.
Includes bibliographical references (p. 317-341) and indexes.
Keywords: Assessment centers (Personnel management procedure)